Integration of Tauhid (Faith) Element in Biology Education - Mohd Salehudin, Sayyidah Nusaibah; H Iksan, Zanaton (Journal of Educational Sciences, 2017)
Tauhidik science is one of the Islamization of Knowledge effortsin the field of education. This effort was initiated by many Islamic scholarsto fight against secularism. To implement the elements of faith (Tawhid) inScience Education, Al-Qur'an is the ultimate guide. The aim of this conceptpaper is to describe the elements of faith in biology education. In thisconcept paper, the definition of Tauhidik Science is specified. Next, thestrategy of integration of Tauhidic element in Biology is explained. Theconcept paper also proposes that the implementation of elements of faithmade in more in-depth for each subtopic studied. The implementation ofFaith element in Science Education is expected to produce a generationwhose life is guided by the Quran and have Ulul Albab thought whichmeans having a deep rooted knowledge and strong belief to Allah s.w.t, thusforming the next generation that brings prosperity to the mankind.